2021
DOI: 10.1016/j.lanwpc.2021.100297
|View full text |Cite
|
Sign up to set email alerts
|

Population-based analysis of the epidemiological features of COVID-19 epidemics in Victoria, Australia, January 2020 – March 2021, and their suppression through comprehensive control strategies

Abstract: Background Victoria experienced the greatest burden of COVID-19 in Australia in 2020. This report describes key epidemiological characteristics and corresponding control measures between 17 January 2020 and 26 March 2021. Methods COVID-19 notifications made to the State Government Department of Health were used in this analysis. Epidemiological features are described over 4 phases, including enhancements to testing, contact tracing and public health interventions. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The first COVID‐19 wave in Victoria was linked with returned overseas travellers, the second wave with inadequate quarantining of returned overseas travellers in hotel quarantine in Melbourne. 3 Early outbreaks during the second wave were initially restricted to ten suburbs, subject to strict lockdown restrictions announced on 29 June 2020, 11 and nine housing towers in North Melbourne and Flemington (about 3000 residents), subject to lockdown from 9 July 2020. 12 These targeted containment measures were unsuccessful, and rapid transmission ensued across metropolitan Melbourne and, to a lesser extent, regional Victoria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first COVID‐19 wave in Victoria was linked with returned overseas travellers, the second wave with inadequate quarantining of returned overseas travellers in hotel quarantine in Melbourne. 3 Early outbreaks during the second wave were initially restricted to ten suburbs, subject to strict lockdown restrictions announced on 29 June 2020, 11 and nine housing towers in North Melbourne and Flemington (about 3000 residents), subject to lockdown from 9 July 2020. 12 These targeted containment measures were unsuccessful, and rapid transmission ensued across metropolitan Melbourne and, to a lesser extent, regional Victoria.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small first wave (25 January to late 9 April 2020) was dominated by infections acquired overseas (59.5% of cases). 3 The second wave, which commenced in May 2020, was characterised by locally acquired infections (91% of cases); genomic sequencing indicated that the two transmission networks during this wave originated with infected people in hotel quarantine. 3 To reduce community transmission, the Victorian government introduced compulsory mask‐wearing, curfews, travel restrictions, closure of non‐essential businesses, and limits on the permitted number of household visitors.…”
mentioning
confidence: 99%
“…Recall that the model used the active-case R eff to characterise local transmission at the time of forecast, with transmission reverting to the transmission potential (TP) over time (see Section 4.2 for details; example R eff trajectories are shown in Section B.4). However the second wave in Victoria was dominated by localised outbreaks in health and aged care settings, and other essential services, where public health and social measures to constrain transmission had less impact than in the general population [5]. Over a 5-month period, the R eff was systematically greater than the TP, as described and evaluated in Golding et al [7].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of infected persons that were identified as cases was likely to be both very high, and to remain relatively constant over the study period. These cases include asymptomatic individuals who were identified through large-scale and systematically exhaustive contact tracing programs [5]. In comparison, in recent influenza seasons the probability that a person with influenza-like illness (ILI) symptoms would seek healthcare and have a specimen collected for testing (as estimated from Flutracking [32, 33] survey participants) was around 3–8% [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation